2008
DOI: 10.1007/s00213-008-1084-0
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance of healthy young rats following chronic donepezil administration

Abstract: The present findings show the specific profile of donepezil action on cognitive functions in the presence of unaltered cholinergic neurotransmission systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 67 publications
2
15
1
Order By: Relevance
“…It is possible that the dose of donepezil was not optimal and that lower or higher doses would be more effective. Lower doses (≤1.0 mg/Kg/day) have been shown to enhance performance of young and aged rats on other spatial tasks including delayed visual matching to sample (Bennett, et al, 2006), Morris water maze (Cutuli, et al, 2008; Cutuli, et al, 2009; Hernandez, et al, 2006), object recognition (Prickaerts, et al, 2005), and radial arm maze (Cutuli et al, 2008; Cutuli et al, 2009) tasks. Donepezil at >1.0 mg/Kg has been shown to reduce impairments on a Morris water maze task in young rats treated with scopolamine (Takahata, et al, 2005), and in a rat model of encephalomyelitis (D’Intino, et al, 2005); however, not all studies have observed beneficial effects of donepezil on cognitive performance (Barnes et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the dose of donepezil was not optimal and that lower or higher doses would be more effective. Lower doses (≤1.0 mg/Kg/day) have been shown to enhance performance of young and aged rats on other spatial tasks including delayed visual matching to sample (Bennett, et al, 2006), Morris water maze (Cutuli, et al, 2008; Cutuli, et al, 2009; Hernandez, et al, 2006), object recognition (Prickaerts, et al, 2005), and radial arm maze (Cutuli et al, 2008; Cutuli et al, 2009) tasks. Donepezil at >1.0 mg/Kg has been shown to reduce impairments on a Morris water maze task in young rats treated with scopolamine (Takahata, et al, 2005), and in a rat model of encephalomyelitis (D’Intino, et al, 2005); however, not all studies have observed beneficial effects of donepezil on cognitive performance (Barnes et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…[27]. We previously demonstrated that healthy rats treated with donepezil during behavioral testing showed enhanced memory and explorative functions in RAM and OF, as well as reduced anxiety levels in EPM, but they did not exhibit any improvement in spatial span, motivational levels and associative learning [41]. Thus, although donepezil treatment during testing is able to improve cognitive performance even in unlesioned animals, donepezil treatment before testing (pre-treatment) exerts neuroprotective action only in the presence of lesion or insult.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, only a small number of studies have investigated the effects of donepezil on uncompromised rodents, although many of the reported effects of donepezil were similar. For instance, chronic administration of donepezil (0.5 mg/kg then 0.2 mg/kg) in uncompromised male rats was shown to enhance acquisition and performance on several spatial and nonspatial memory and attention tasks (Cutuli et al, 2008). Doses of 0.3 and 1 mg/kg of donepezil were also reported to decrease the number of errors emitted in a two-phase radial-arm maze procedure compared to control in male rats (Wise et al, 2007).…”
Section: Discussionmentioning
confidence: 99%